(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
قمنا في هذا البحث بدراسة تأثير ضغط المزيج الغازي المكوّن من الهيدروجين والأرغون على الخصائص الكهربائية والضوئية للأفلام الرقيقة (ذات السماكة الأكبر من) المحضرة من السيلكون المهدرج غير المتبلور (a-Si:H) وأشكال دخول الهيدروجين فيها. ودرسنا أيضاً أثر زيادة سماكة طبقات السيلكون المهدرج غير المتبلور على كثافة الحالات المتوضعة في الفجوة الطاقية. وعيَّنا القيمة الحدية لضغط المزيج الغازي الموافقة للقيمة العظمى لنسبة الناقلية الضوئية إلى الناقلية المظلمة، والتغير الحاد في متحولات الناقلية المظلمة، ومعطيات أطياف امتصاص الأشعة تحت الحمراء لهذه الطبقات. أضف إلى ذلك قمنا بحساب طاقة يورباك للأفلام الرقيقة a-Si:H ، واستنتجنا عدم إمكانية استخدامها في طبقات التصوير الكهربائي أحادية التركيب لأنها لا تتصف بالمقاومة النوعية المظلمة اللازمة لذلك. وأخيراً حصلنا على منحني التفريغ في حالة الظلام لطبقات التصوير الكهربائي ثلاثية التركيب حيث ازداد الكمون الأولي للشحَن بمقدار 68 V وتجاوز زمن التفريغ 10 s عند زيادة سماكة طبقات كربيد السيلكون المهدرج غير المتبلور (a-SiC:H) من القيمة إلى. In this research, we studied the effect of the pressure of a mixture of Argon-Hydrogen gas on the electrical properties and photo-properties of thin films (thickness) prepared from amorphous hydrogenated silicon (a-Si:H) and the forms of the incorporation of hydrogen to it. Also, we studied the influence of increasing the thickness of a-Si:H layers on the density of localized states in energy gap. Then, we determined the critical value of the gas mixture pressure, which is consistent with maximum value of the ratio of the photoconductivity to dark conductivity, the critical change of dark conductivity parameters and, IR-absorption spectrum data of these layers. Also, we calculated Urbach’s energy of a-Si:H thin films and concluded the impossibility of using them in single structured electrophotography layers, because they don’t have the required enough dark specific resistance. Finally, we were able to get the discharge curve in the darkness case of the triple structured electrophotography layers, where the initial discharge potential increased by 68 V and the discharge time overreached 10 s for this curve, when the thickness of amorphous carbide silicon (a-SiC:H) layers increased from to.